Identifying the causes of self-harm in adolescent girls in the socio-cultural context of Kermanshah - seiedeh sahar hoseini; Mohamad Sajjad Seydi; Mohsen Golmohamadian (Kerman University of Medical Sciences, 2021)
Introduction: Due to the harmful nature of self-harm, studying in this field is especially important in adolescents. The objective of this study was to identify the causes of self-harm in adolescent girls in the socio-cultural context of Kermanshah. Methods: This qualitative and phenomenological study was conducted in 2017 and the participants in the study were 21 adolescent girls with a history of self-harm that were selected using snowball sampling method-.  Collaizi's seven-step method was used for qualitative analysis of texts. Results: The semantic units of the interviews were categorized into 135 conceptual codes. The themes related to the causes of self-harm were classified into three categories: a. Family- related factors including poor verbal communication among family members, neglect and lack of love, discrimination between the sexes, parental control, type of family upbringing, threats from the mother, fear of the father, being indifferent, and etc., b. Environmental factors and conditions including taking friends as role models, being fashionable, being provoked by sad songs, being influenced by violent movies death of the relatives, taking role models from cyber space, etc., and c. Individual Factors including finding grandeur, proof of courage, loneliness, nervousness, interest in experiencing, impulsiveness, relationship with the opposite sex, emotional failure, and drawing attention. Conclusion:  The results of this study revealed that adolescents see self-harm as a way to get rid of negative emotions or get back their neglected rights. Having disputes with parents, being overwhelmingly influenced by friends and peers, and having severe mental conditions all play a significant role in causing self-harm.